Gambaran Derajat Dismenore dan Upaya Mengatasinya di Pondok Pesantren Darussalam Al-Hafidz Kota Jambi - Ria Febrina (Jurnal Akademika Baiturrahim Jambi, 2021)
Dysmenorrhea is a menstrual disorder that is often experienced by young women. Dysmenorrhoea is characterized by lower abdominal pain and may be accompanied by other symptoms. The incidence of dysmenorrhea in Indonesia consists of primary dysmenorrhea 54.89% and secondary dysmenorrhea 9.36%. Dysmenorrhea can have a negative impact on young women, namely disruption in teaching and learning activities so that it will affect academic or academic achievement. This study is to describe the degree of dysmenorrhea and the efforts to overcome it in the Darussalam Al-Hafidz Islamic Boarding School, Jambi City. This type of quantitative research with a descriptive design. Respondents who have experienced dysmenorrhea as many as 31 respondents were sampled in this study.The data collection technique was done by filling out a questionnaire. The data is presented in a frequency distribution table. The results of the study most of the respondents experienced a degree of mild pain dysmenorrhea as many as 80.6% of respondents, most of the efforts to treat dysmenorrhea by non-pharmacological means by applying balsam or lotion as much as 71.0%. Most of the respondents experienced mild pain dysmenorrhea and Most of the efforts to treat dysmenorrhea are non-pharmacological by applying balsam or lotion